Improving Meat Quality and Reducing Breast of Myopathies in Broiler Chickens Subjected to Cyclic Heat Stress by Supplementing of Chromium-Methionine - Tesser, G. L. S.; Rohloff Junior, N.; Andrade, T. S.; Kaufmann, C.; Costa, A. P. G. C.; Pereira, M. F. C.; Calderano, A. A.; Dadólio, F. S.; Klosowski, E. S.; Eyng, C.; Nunes, R. V. (Faculty of Animal Science, IPB University, 2025)
Chromium-methionine (CrMet) provides essential nutrients and bioactive compounds that may enhance meat quality and reduce stress-related issues in broiler chicken. This study aimed to evaluate the effects of chromium-methionine on carcass yield, relative weights of the liver and fat pad, incidence and severity of myopathies, muscle color quantification, water-holding capacity, cooking loss, shear force, lipid peroxidation in breast muscle, and composition of breast meat in broiler chickens subjected to cyclic heat stress. A total of 1,000 one-day-old male Cobb 500 broiler chickens were divided into 10 replicate pens with 20 birds each, following a completely randomized design with five doses of dietary treatments (0; 0.25; 0.50; 1.0; and 2.0 mg CrMet kg-1 diet). Experimental broiler chickens were kept in thermoneutral conditions for 21 days, then subjected to cyclic heat stress (31.1 °C and 60.2% humidity) from 09:00 am to 03:00 pm until 42 days of age. Statistical analysis included Tukey’s test and regression analysis. Myopathy scores were assessed using the Kruskal-Wallis test and Dunn’s test, all at a significant level of 5%. Inclusion of 0.50 and 1.0 mg CrMet reduced woody breast severity scores. At 15 minutes postmortem, birds fed 0.50 mg CrMet had less redness (a*) than controls and birds fed 2.0 mg CrMet; birds fed 2.0 mg CrMet had lower lightness (L*) than those fed 0.25 and 1.0 mg CrMet. Lipid peroxidation was lower in birds fed 0.50 mg CrMet at 60 days compared to control. Crude fat was lower in birds fed 1.0 mg CrMet. Chromium-methionine supplementation at 0.50 and 1.0 mg/kg diet improved meat quality and reduced woody breast in broiler chickens.